La quantificació: estudi comparatiu castellà-català - Camus Bergareche, Bruno (Caplletra. Revista Internacional de Filologia, 2005)
Taking as a point of departure the classification of modern Spanish quantifiers, the paper opens with a brief description of the inventory of these items in medieval language and the basic traits of their syntactic evolution. The same discussion is madefor equivalents words in modern and medieval Catalan in order to establish a picture of the significant evolutionary differences between both languages. Finally, for the sake of a future historical syntax of Catalan, we offer a little catalogue of research proposals on this area of Catalan quantifiers.